THE ROLE OF MNEMIC ACTIVITY IN STATEMENT WRITING - Kholikulova, Feruza (Журнал иностранных языков и лингвистики, 2023)
Over the years, the development of speech skills and relevant knowledge at the expense of memory known in the sequence o’rnashuvchi words related to mastering a growing backup. Children 4–5 up to the age of the memory during the period under certain speech the word is formed within the base. This material is relevant to a particular situation of children, in case any image or automatic speech in’ikosini own finds. The speech of the student, his level communicative literacy mushohada be doing independent and creative, which will help to represent mnemik correct and fluent thinking skills activity associated with the show. “Mnemik business – the essence of things and events, the type of material relevant to the content remember, recall and remember keep be launched to be associated with the complex activity type”[1]is. [1] https://fayllar.org/toshkent-davlat-iqtisodiyot-universiteti-v8.html?page=9